IMPLEMENTASI VISI RIAU 2020 PADA LEMBAGA ADAT MELAYU RIAU - Mosthamir Thalib (Universitas Riau, 2016)
Implementation of Vision 2020 in Riau Lembaga Adat Melayu Riau. This study aims to explain the Government’s efforts through the Institute of Adat Melayu Riau Riau Riau implementing Vision 2020 and the obstacles that occur in the implementation of the Vision 2020 Riau. This research is qualitative. Data collected through the study of documentation and interviews with informants informants research comes from the Government of Riau Province, LAM and Society. The data were analyzed descriptively kualitatiif. The study concluded that efforts Lembaga Adat Melayu Riau in implementing policies related to the development, preservation and development of Malay culture shows that the communication be the determining factor. While the resources and disposition contribute not much different. Is a constraint in the implementation of this policy is the development of resources, especially relating to budgetary resources and human resources.